The LDL-Receptor and its Molecular Properties: From Theory to Novel Biochemical and Pharmacological Approaches in Reducing LDL-cholesterol - Petroglou, Dimitrios; Kanellos, Ilias; Savopoulos, Christos; Kaiafa, Georgia; Chrysochoou, Anastasios; Skantzis, Panagiotis; Daios, Stylianos; Hatzitolios, Apostolos I.; Giannoglou, Georgios (Current Medicinal Chemistry, 2020)
Background: The Low-Density Lipoprotein (LDL) Receptor (LDL-R) is a transmembrane protein playing a crucial role in effective lipid homeostasis. Various therapeutic agents have been used in the management of dyslipidemias, however, the outcome of therapeutic target is debated. Objective: The aim of this review is to summarize and fully understand the current concept regarding LDL-R and its molecular properties, metabolic pathway, factors affecting LDL-R activity and all available pharmacological interventions. Additionally, non-lipid related properties of LDL-R are also referred. Methods: Literature from the PubMed database was extracted to identify papers between 1984 to 2017 regarding LDL-R and therapeutic agents on dyslipidemia management. Results: We analyzed basic data regarding agents associated with LDL-R (Sterol Regulating Element-Binding Proteins - SREBPs, Protein ARH, IDOL, Thyroid Hormones, Haematologic Disorders, Protein convertase subtilisin kexintype 9 - PCSK-9, ApoC-III) as well as non-lipid related properties of LDL-R, while all relevant (common and novel) pharmacological interventions (statins, fibrates, cholesterol absorption inhibitors, bile acid sequestrants and PCSK- 9) are also referred. Conclusion: LDL-R and its molecular properties are involved in lipid homeostasis, so potentially sets the therapeutic goals in cardiovascular patients, which is usually debated. Further research is needed in order to fully understand its properties, as well as to find the potential pharmacological interventions that could be beneficial in cholesterol homeostasis and various morbidities in order to reach the most appropriate therapeutic goal.
Keywords: sterol regulating element-binding proteins (SREBPs)